Formulation of liposomes using microfluidics flow reactors fabricated using 3D printing technology. - Bin Haru, Reshad.; Xu, Qiaobing.; Jiang, Xioacheng.; Glass, Zachary.; Hsu, Leo. (Tufts University. Tisch Library., 2017)
Drug Delivery Technology market is expected to grow to 1.5 Tr USD by 2020, underpinning the huge need for injectible drugs. One of the key parameters to maximize for drug delivery is efficiency of delivery. Liposomes allow very efficient delivery of drugs, but currently creating liposome encapsulated drug delivery is not scalable or rapid. This is where microfluidics comes in - microfluidics allows a single step high-throughput production of liposomes encapsulating payload. Microfluidics involves a clever choice of microreactor channel geometry, and flow rate manipulation at the microscale to create liposomes in large quantities and with a fixed size distribution. The channel geometry and dimensions are selected such that fluid flow occurs at the microscale at low Reynold’s number. The uniform interface of two or more flows allow for mixing at controlled ‘residence times’ which allows for control on size of the liposome created. A low polydispersity index, which is a measure of the liposome size distribution, allows for more control on targeting specific tissues and organs. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.